The Influence of the Family Environment on Student Learning Outcomes in Class IV Social Studies Content di SDN 38 Ampenan - Jumiarti Jumiarti (Jurnal Syntax Admiration, 2023)
The family environment greatly influences students' success in achieving good learning outcomes. This is reinforced by the theory in Djaali's book; Family situations (father, mother, siblings, younger siblings, older siblings, and extended family) have a significant impact on a child's success within the family. Parental education, economic status, home environment, the percentage of parental relationships, words, and parental guidance all influence a child's learning achievements. This study aims to determine the influence of the family environment on student learning outcomes in the Social Studies subject for fourth-grade students at SDN 38 Ampenan. This research falls under the category of population research and is Expost Facto in nature. The study was conducted at SDN 38 Ampenan in fourth-grade classes, consisting of parallel classes IV/A and IV/B, during the academic year 2022/2023. The data collection instrument used was a family environment questionnaire and data on student test scores in the Social Studies subject. The family environment indicators used include parenting styles, family member relationships, home atmosphere, family economic conditions, and parental understanding. The data analysis techniques employed include descriptive statistical tests, tests for homogeneity, normality, and hypothesis testing. Hypothesis testing uses simple linear regression. The research results show that the significance value obtained is less than 0.005, and the calculated t-value is greater than the tabulated t-value. This indicates that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, suggesting a significant influence of the family environment on student learning outcomes in the Social Studies subject at SDN 38 Ampenan.